The success of social network in global awareness about e-waste education - Mbagurire, Jean Pierre (2011)
It is known that e-waste management is among the highest challenges to implement green IT from its definition. Due to its toxicity, human life and environment will be in danger if we fail to reduce the amount of e-waste generated nowadays. The sensitization should focus now on end users and make them realize the problem. As a result, this will help people to change the culture of throwing away some assets which may be needed by neighbors or keep unused devices, while other people are looking for similar ones. In this situation, Social networks are suitable tool that may work better for that awareness process to reach many people instantly. The success of social networks is based on the fact that people have the specific ways to talk and understand each other on their respective groups. And this is an opportunity that will make awareness to be successful once introduced by one member among the group.